Insulin receptor tyrosine kinase activity in colon carcinoma - Corleta, Helena von Eye (2022)
Colon carcinoma is the most common tumor of the gastrointestinal tract. According to some investigators, insulin, epidermal growth factor (EGF) and insulin-like growth factor I (IGF-I) may be involved in the neoplastic proliferation. Insulin-binding and receptor tyrosine kinase activity were investigated in colon carcinomas and in normal colons. The insulin receptor concentration, as shown by binding assays, was 17.4 ± 4.3 fmol/J.Lg in normal colon and 29.69 ± 9.4 fmol/ J.Lg in colon carcinoma. Nevertheless, the insulin affinity of the receptor was similar in both groups (Kd ::: 1 nM). Both normal and neoplastic colon showed phosphorylation of the insulin receptor. The electrophoretic migration of the B-subunit of the insulin receptors purified from colon carcinomas was similar to that of normal colon and both tissues demonstrated an insulin-dependent autophosphorylation. The receptor tyrosine kinase activity was measured by the incorporation of[gamma32P]ATP into the B-subunit. The basal and the insulin-stimulated tyrosine kinase activities were significantly higher in colon carcinomas compared to normal colon tissues (2.2 and 1.6 times, respectively). Understanding the metabolism of neoplastic cells may contribute to the development of prevention strategies as well as new therapies. It is now necessary to study other steps of the insulin signal transduction pathway, such as insulin receptor substrate 1 phosphorylation.